ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL GROVER, ALTMAN Z-SCORE, SPRINGATE, DAN ZMIJEWSKI PADA PERUSAHAAN TELEKOMUNIKASI - Setyaningsih Sri Utami, Elly Rahmawati, Suprihatmi Sri Wardiningsih & (Universitas Slamet Riyadi, 2018)
This study aims to find out the predicted results of Grover, Altman Z-Score, Springate and Zmijewski models in predicting financial distress and knowing the accurate model used in telecommunication companies in Indonesia. This study compares the financial distress prediction model by analyzing the accuracy of each model. The data used in this research is the annual financial report of the company which is published by Bursa Efek Indonesia period 2013 - 2016. The sampling technique is purposive sampling with total sample of 4 companies. The results of this study note that Grover model has an accuracy of 100% with an error rate of 0%, Altman Z-Score has an accuracy of 87,5% with a 12,5% error rate, Springate has an accuracy of 81,25% with a 18,75% error rate, while Zmijewski has an accuracy of 87,5% with an error rate of 12,5%. Of the four models of bankruptcy analysis used in this study can be concluded that the Grover model is an accurate model used to detect bankruptcy because it has the highest accuracy of 100% with an error rate of 0%.Keywords: financial distress, grover, altman z-score, springate, zmijewski